Cancer incidence and mortality in China, 2013. (10th August 2017) - Chen, Wanqing; Zheng, Rongshou; Zhang, Siwei; Zeng, Hongmei; Xia, Changfa; Zuo, Tingting; Yang, Zhixun; Zou, Xiaonong; He, Jie
Abstract: Objective: National Central Cancer Registry of China (NCCRC) updated nationwide statistics of cancer incidence and mortality in China using population-based cancer registration data in 2013 from all available cancer registries. Methods: In 2016, 255 registries' data were qualified and included in this analysis. We estimated numbers of new cancer cases and deaths in China in 2013 using age-specific rates and corresponding national population stratified by area, sex, age group (0, 1–4, 5–9, 10–14…85+) and cancer type. The world Segi's population was applied for age-standardized rates. All rates were expressed per 100, 000 person-year. Results: A total of 3, 682, 000 new cancer cases and 2, 229, 300 cancer deaths were estimated in China in 2013. Cancers of lung, female breast, stomach, liver, colon-rectum and esophagus were the most common cancers, accounting for about half of all cancer new cases. Lung cancer, liver cancer, stomach cancer, esophageal cancer, colorectal cancer were the five leading causes of cancer death, accounting for about 60% of all cancer deaths. The cancer patterns showed differences not only between male and female, but also among different geographic regions in China. For overall cancers, the age-standardized incidence rates were stable during the past decades in male, but significantly increased by 2.2% per year in female. Conclusions: Cancer poses a major threat to public health and the cancer burden keep raising in China. The annual updated cancer statistics can provide scientific basis for cancer prevention and control. Highlights: Most cancer registries in history. Most recent cancer statistics in China. New cancer cases were 3.68 millions in 2013 in China. Lung cancer is the most common and leading of childhood cancer. Cancer incident cases and deaths keep increasing.